#### Answer

-1

#### Work Step by Step

By the definition of $i$ shown on Page 485, we know that $\sqrt -1=i$ because $i^{2}=-1$.
Therefore, $(-i)^{2}=(-i\times-i)=(i\times i\times-1\times-1)=(i^{2}\times-1\times-1)=(-1\times-1\times-1)=-1$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.